Một số kết quả nghiên cứu chế tạo hệ sơn nước bảo vệ kết cấu bê tông cốt thép khu vực biển và ven biển - Bích Thuỷ, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
This article is about our research on two different kinds of waterborne paint: acrylic and epoxy paints ideally for making anticorrosive coatings of steel reinforced concrete in marine and maritime environment. Using water as the main solvent, these paints with low organic solvent are normally non odor. Our empirical tests show that they fulfilled all requirements of 22TCN 235-97 and TCVN 6934:2001, the Vietnamese technical standards governing building materials for protection of concrete or steel reinforced concrete in the maritime climate area. Keywords: Waterborne paint, Acrylic and Epoxy paints, Maritime environment, Steel reinforced concrete.